The Corruption Reduction with an Administrative Law Approach: Evidence from Australia - Hafidz, Jawade; Amalia Fitri, Dini; Muhammad Azam; Arifullah, Achmad; Prasetia Wiranto, Agus (Lembaga Contrarius Indonesia, 2024)
The reverse burden of proof mechanism shifts the responsibility to the fraudster to prove that his wealth did not come from corruption. This system raises concerns regarding justice, legal certainty, and the protection of human rights. This research aims to analyze the application of reverse evidence in criminal and criminal acts of corruption in procuring goods and services from the perspective of state administrative law. Reversal of the burden of proof in criminal acts of corruption is essential to eradicate corruption in Indonesia. From the standpoint of state administrative law, reverse evidence functions as a monitoring tool to prevent abuse of authority by public officials and ensure the implementation of the principles of good governance, namely transparency, accountability, and integrity in the procurement of goods/services. The novelty of this study lies in its proposal to explicitly clarify the balance of evidentiary obligations between the public prosecutor and the defendant in reversing the burden of proof under Law No. 20 of 2001, ensuring fair legal certainty and protection of human rights. Indonesia can adopt Australia's Proceeds of Crime Act 2002 approach, enabling asset seizure from suspected corruption without conviction, to enhance accountability and recover state losses effectively.